KESANTUNAN BERBAHASA JEPANG OLEH STAF GRO DI BIRO PERJALANAN WISATA DI BALI - Dewi, Ni Made Andry Anita (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
Politeness is one important aspect in realizing polite speech. Polite speech is the basic matter for providing services to Japanese tourist by workers who working for tourism industry. The focus of this research is to identify and research the Japanese politeness which is used by speakers of Japanese who works in a travel agency in Bali for providing services to Japanese tourists. The methodology used in this research is interview. The informans were seven of guest relations officer (GRO) staff in a travel agency in Bali. This research is examined by using the six principles of politeness based on Leech’s classification (1983). They are 1) tact maxim; 2) generosity maxim; 3) approbation maxim; 4) modesty maxim; 5) agreement maxim; and 6) sympathy maxim.
Keywords: Japanese of polite speech, Leech’s classification, and maxim